Terapi Okupasi Memasang Tali Sepatu terhadap Motorik Halus pada Anak Tunagrahita Sedang - Mochamad Heri; Ni Made Dwi Yunica Astriani; Komang Gde Trisna Purwantara; Putu Devi Kurnia Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the effect of occupational therapy on attaching shoelaces to the improvement of fine motor skills in mentally disabled children in SLB N 1 Badung. This research method is quantitative research with pre-experimental research design pre-post test one group design. The result of univariate analysis of the intervention of 41 respondents before being given occupational therapy for fine motor development was 1.20, and after being given occupational therapy, fine motor development was 1.41. The results of this study showed the average fine motor development during the pre-test was 1.20. After being given the occupational therapy treatment of attaching shoelaces, the average fine motor development was 1.41. Data analysis results with the Wilcoxon test get a value of 0.003 or p <Î± (0.05). In conclusion, occupational therapy influences placing shoelaces on fine motor skills in children with moderate mental retardation in SLB N 1 Badung. Keywords: Fine Motoric, Occupational Therapy, Impairment